The freedom and responsibility in philosophy (Journal of Philosophy Culture and Political Science, 2015)
Responsibility and freedom as existentially vital categories are considered from a religious, ethical, legal, historical parties and will be explored further in the future. These philosophical concepts characterize the importance of human life. Responsibility and freedom to help the development of human knowledge as a result of the examination, experiment and observation.Responsibility - is imposed on anyone or taken by someone obligation to give aware of their actions and to take the blame for the consequences. We are always responsible for their own and others' lives, freedom is responsibility does not exist, they interact.
Keywords: humanism; responsibility; guilt; freedom; debt.